Computational Elements for High-fidelity Aerodynamic Analysis and Design Optimisation - Kim, Chongam (Defence Science Journal, 2010)
The study reviews the role of computational fluid dynamics (CFD) in aerodynamic shape optimisation, and discusses some of the efficient design methodologies. The article in the first part, numerical schemes required for high-fidelity aerodynamic flow analysis are discussed. To accurately resolve high-speed flow physics, high-fidelity shock-stable schemes as well as intelligent limiting strategy mimicking multi-dimensional flow physics are essential. Exploiting these numerical schemes, some applications for 3-D internal/external flow analyses were carried out with various grid systems which enable the treatment of complex geometries. In the second part, depending on the number of design variables and the way to obtain sensitivities or design points, several global and local optimisation methods for aerodynamic shape optimisation are discussed. To avoid the problem that solutions of gradient-based optimisation method (GBOM), are often trapped in local optimum, remedy by combining GBOM with global optimum strategy, such as surrogate models and genetic algorithm (GA) has been examined. As an efficient grid deformation tool, grid deformation technique using NURBS function is discussed. Lastly, some 3-D examples for aerodynamic shape optimisation works based on the proposed design methodology are presented. Defence Science Journal, 2010, 60(6), pp.628-638, DOI:http://dx.doi.org/10.14429/dsj.60.581